A MODEM FUNCTION FOR DYNAMIC RESPONSE SCHEDULING OPTIMIZATION IN MOBILE EDGE COMPUTING ARCHITECTURE FOR IOT BASED DEVICES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The Internet of things (IoT) describes devices with sensors, processing ability, software and other technologies that connect and exchange data with other devices and systems over the Internet or other communications networks.[1] The Internet of things encompasses electronics, communication, and computer science engineering. "Internet of things" has been considered a misnomer because devices do not need to be connected to the public internet; they only need to be connected to a network[6] and be individually addressable.[7]